Designing social science teaching materials with a culturally responsive teaching approach in elementary schools - Purnamasari, Iin; Ginting, Rosalina; Cholifah, Nur; Sajat, Nofazilah binti Mohd (Jurnal Konseling dan Pendidikan, 2025)
The research aims to describe how to design social studies teaching materials based on local wisdom with a Culturally Responsive Teaching approach. The research uses a qualitative descriptive approach. The procedure starts with determining the subject, namely the teacher; data collection from questionnaires and interviews on the use of teaching materials; reduction of the results of filling out questionnaires and interviews; classification, how to make, and understanding the importance of local wisdom as content of teaching materials; followed by the presentation of data and the drawing of conclusions. The research instrument used an analysis questionnaire of teaching materials and interview guidelines. Previous research shows that social studies teaching materials are still textual and have not yet contained local wisdom of the community as social and cultural capital. The study results explain how to design social studies teaching materials based on local wisdom with the CRT approach. The design of teaching materials with the CRT approach contains the values of local wisdom from the immediate environment of students. Developing teaching materials is carried out by analyzing Learning Outcomes, selecting social skills elements, determining social studies topics, and selecting local wisdom in the form of students' regions' social and cultural capital. Furthermore, the steps in designing teaching materials based on local wisdom with the CRT approach start from recognizing student culture, integrating cultural content, using varied methods, presenting diverse materials, and facilitating student involvement. The use of local wisdom with the CRT approach makes it easier for students to understand the broad concept of social studies.